Governança das organizações de territórios impactados por usinas hidrelétricas no Brasil. - Finkler, Sandra (2022)
This dissertation Governance of Organizations of Territories Impacted by Hydroelectric Plants in Brazil, presents a study on the existing territorial governances in areas impacted by dams created for the generation of hydroelectric energy. The objective was to identify existing organizations in territories flooded by hydroelectric power plants and the functioning of these organizations in the territory, as well as their functioning and the most common organization formats. Through the data collected and their comparison, it can be seen that there are few organizations created for territorial development in impacted areas. The methodology used was the collection of secondary data from existing documents and bibliographies related to the proposed themes. Among the two hundred and nineteen existing hydroelectric power plants in Brazil, only fifteen organizations were identified, and of these, only ten organizations had the characteristics sought, which are located in Minas Gerais, Paraná and Santa Catarina. Among the 10 organizations analyzed, it was found that nine are non-profit associations and one is a consortium. Nine are made up only of city halls and one also has city councils and trade associations in its membership. It was noted through the collected data that those that have project rooms and work in partnership with multipurpose consortia are the ones that present the best performance. With data on the functioning of these organizations and with the theoretical basis focused on territory, territorial development, sustainable development, governance, public policies and networks, we sought to present a model of governance with the use of cooperation networks, the SDGs and the agenda 2030, which is a global development proposal, involving all actors in the territory, seeking better results for development. The last chapter presents the territorial governance model with the use of technical cooperation networks as a key tool for the best performance of organizations created for the development of a territory.